Laboratory detection of the antiphospholipid syndrome via calibrated automated thrombography - Devreese, Katrien; Peerlinck, Kathelijne; Arnout, Jef; Hoylaerts, Marc F. (Thrombosis and Haemostasis, 2009)
Lupus anticoagulants (LAC) consist of antiphospholipid antibodies, detected via their anticoagulant properties in vitro. Strong LAC relate to thromboembolic events, a hallmark of the anti-phospholipid syndrome. We have analyzed whether detection of this syndrome would benefit from thrombin generation measurements. Therefore, calibrated automated thrombography was done in normal plasma (n=30) and LAC patient plasma (n=48 non-anticoagulated, n=12 on oral anticoagulants), diluted 1:1 with a normal plasma pool. The anti-β2-glycoprotein I monoclonal antibody 23H9, with known LAC properties, delayed the lag time and reduced the peak height during thrombin generation induction in normal plasma dose-dependently (0–150 μg/ml). At variance, LAC patient 1:1 plasma mixtures manifested variable lag time prolongations and/or peak height reductions. Coupling these two most informative thrombin generation parameters in a peak height/lag time ratio, and upon normalization versus the normal plasma pool, this ratio distributed normally and was reduced in the plasma mixtures, for 59/60 known LAC plasmas. The normalized peak height/lag time ratio correlated well with the normalized dilute prothrombin time, diluted Russell’s viper venom time and silica clotting time, measured in 1:1 plasma mixtures (correlation coefficients 0.59–0.72). The anticoagulant effects of activated protein C (0–7.5 nM) or 23H9 (0–150 μg/ml), spiked in the 1:1 LAC plasma mixtures were reduced for the majority of patients, compatible with functional competition between patient LAC and activated protein C and LAC and 23H9, respectively. Hence, the normalized thrombin generation-derived peak height/lag time ratio identifies LAC in plasma with high sensitivity in a single assay, irrespective of the patient’s treatment with oral anticoagulants.
Keywords: Thrombosis; α2-glycoprotein I; lupus anticoagulants; prothrombin; antibodies